2018
DOI: 10.1097/sih.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Simulation Training Reduces Intraoperative Cataract Surgery Complications Among Residents

Abstract: The addition of surgical simulation training was associated with a significantly reduced rate of complications, including posterior capsule tears and vitreous prolapse, among novice postgraduate year 3 residents. There is a perceived utility among residents to incorporate virtual simulation into surgical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 30 publications
1
61
0
4
Order By: Relevance
“…Only the study from Staropoli et al 14 had all bias items identified as low risk. The study by Staropoli et al was also the only study that had a protocol which enabled appraisal of its reporting bias.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Only the study from Staropoli et al 14 had all bias items identified as low risk. The study by Staropoli et al was also the only study that had a protocol which enabled appraisal of its reporting bias.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Regarding patient outcomes, five studies demonstrated the transfer effects of Eyesi with reduced complications in live cataract surgery following training [ 12 , 21 , 29 , 35 , 38 ]. Of note, a multi-centre retrospective study involving 265 ophthalmology trainees across the UK showed that complication rates dropped from 4.2 to 2.6% (38% reduction) following the introduction of Eyesi simulators into training programmes [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…An overall increase in operative volume will not overcome these deficiencies occurring at an early stage of surgical training, but rather additional supervision and reassurance are most effective. Parikh et al have cited interesting articles from the ophthalmic 3 and nonophthalmic literature 4,5 showing that surgeons with higher case volumes have better surgical outcomes. However, each of these studies evaluated the outcomes of independent experienced practitioners, and they may not be directly applicable to residents operating under the direct supervision of attending surgeons.…”
Section: Ravi Parikh MD Mph 12 Grayson W Armstrong Md Mph 3 Alementioning
confidence: 99%
“…Last, trainee use of virtual reality simulation has been found to be helpful in avoiding future surgical complications, thus adding to the evidence that increased levels of surgical practice, be it real cases or virtual, are useful in building surgical skill. 5 It may be difficult for programs to increase surgical case volume for struggling residents. Residency programs must ensure that all trainees receive adequate surgical numbers, therefore limiting the amount of surgeries any program can reassign from skilled to less skilled trainees.…”
mentioning
confidence: 99%